GAMBARAN DETERMINAN PERILAKU MASYARAKAT MEROKOK DALAM RUMAH DI WILAYAH KERJA PUSKESMAS X BANYUWANGI - sari, nenda puspita (Majalah Kesehatan Masyarakat Aceh (MaKMA), 2019)
One indicator in PHBS is smoking behavior. This behavior becomes increasingly dangerous if done in the house. The number of smokers that is increasing every year is a concern in itself. This research is a quantitative descriptive study using a cross sectional study design. The research data is taken from K3 and SMD where 20% will be used as the study sample. Data analysis using software to determine the distribution of people who smoke. The results showed that the most common problems were in-house smoking as many as 790 households from 1840 households surveyed, less latrine access utilization as many as 1115 households from 1840 households surveyed, and 69% exclusive breastfeeding or 109 households from 1840 households who in the survey. The reason for respondents to smoking habits is family who smokes even in front of their own children. In addition, cigarettes can make the mind calm. Some respondents claimed to want to quit smoking, either directly or gradually. This condition can be overcome by increasing health promotion to increase self-awareness. Support from parents and friends is also needed to achieve public health.